Rhodium Dopants on Zn2GeO4 Surfaces as Active Sites for Photocatalytic Water Splitting. Issue 2 (12th October 2016) - Wang, Yu Lei; Li, Yu Hang; Wang, Xue Lu; Chen, Ai Ping; Yang, Hua Gui
Abstract: Doping has been widely used to engineer efficient photocatalysts for the water‐splitting process in energy conversion and storage systems. Although composition tuning through heteroatom doping is one of the strategies to enhance photoactivity, the origin of the increased activity by doping remains unclear and most illustrations of its role fall in the band engineering area. Herein, it is reported that the rhodium dopants on the surface of Zn2 GeO4, which affect the band structure negligibly, can act as active sites for water splitting. As a result, the Rh δ+ /Zn2 GeO4 photocatalyst demonstrates excellent stability for up to 460 days and significant enhancement of the photocatalytic activity to that of the undoped photocatalyst. The findings in this work may open the door for a rethink of the detailed principles of dopants in photocatalysis, and highlight a feasible route to fabricating efficient photocatalysts. Abstract : Active surface dopant sites : Rh (Rh δ+ ) dopants on the surface of Zn2 GeO4 act as active sites for water splitting. As a result, the Rh δ+ /Zn2 GeO4 photocatalyst demonstrates excellent stability for up to 460 days and significant enhancement of the photocatalytic activity to that of the undoped photocatalyst (see figure).